Perception of Zoonoses in Dog and Cat Owners in Clinic Veterinary in Villavicencio - Colombia (Orinoquia, 2024)
The objective of this study was to evaluate the perception of zoonosis knowledge among guardians of dogs (Canis lupus familiaris) and cats (Felis catus) at the veterinary clinic El Mundo de la Mascota in Villavicencio, Colombia. A cross-sectional study was conducted through a questionnaire applied to 180 guardians of dogs and cats diagnosed with zoonotic diseases. Data obtained were analyzed descriptively and univariately using IBM® SPSS Statistics version 22 software. The survey revealed that 43.3% (78/180) owned a single pet, and 40.6% (73/180) owned 2 to 3 dogs or cats; the proportion of dogs and cats was 72% (251/347) and 28% (96/347), respectively. Additionally, 46% (125/272) of guardians visited the veterinarian when their pet became ill, while 76% (137/180) of respondents were unaware of the meaning of the term "zoonosis." Furthermore, 19% (69/360) considered saliva a transmission mechanism for these diseases. No significant association was found between study variables. This study demonstrated a lack of knowledge regarding zoonosis among participants and a low perception of its importance, underscoring the veterinarian's role as a source of information and the general population's trust in consulting them in cases of zoonosis.